1999
DOI: 10.1177/105345129903400506
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Strategies for Content-Area Reading Instruction

Abstract: Students with reading disabilities in middle and high school grades need assistance in content-area reading to integrate new information with their prior knowledge, to obtain important information from the text, and to remember what they have read. Thus, content area reading instruction is an important component of all secondary curricula and includes strategy instruction in word identification, vocabulary, and comprehension skills. The purpose of this article is to present an overview of the components of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the content areas of the curriculum, such as science and mathematics, researchers have found that vocabulary knowledge is associated with increased achievement and that vocabulary deficits often serve as a barrier to learning (Baumann, Kame’enui, & Ash, 2003; Sáenz & Fuchs, 2002). Science curricula, in particular, are replete with technical vocabulary terms and concepts that impact students’ understanding of texts and instruction (Bryant, Ugel, Thompson, & Hamff, 1999; Sáenz & Fuchs, 2002) and potentially prohibit equitable access to higher level tasks and processes (Elleman, Lindo, Morphy, & Compton, 2009; Yore, Hand, & Florence, 2004). Yet, this problem presents a fruitful opportunity for science teachers to structure learning experiences through the use of explicit vocabulary instruction (Archer & Hughes, 2011).…”
Section: Effective Science Instruction For Swdmentioning
confidence: 99%
“…In the content areas of the curriculum, such as science and mathematics, researchers have found that vocabulary knowledge is associated with increased achievement and that vocabulary deficits often serve as a barrier to learning (Baumann, Kame’enui, & Ash, 2003; Sáenz & Fuchs, 2002). Science curricula, in particular, are replete with technical vocabulary terms and concepts that impact students’ understanding of texts and instruction (Bryant, Ugel, Thompson, & Hamff, 1999; Sáenz & Fuchs, 2002) and potentially prohibit equitable access to higher level tasks and processes (Elleman, Lindo, Morphy, & Compton, 2009; Yore, Hand, & Florence, 2004). Yet, this problem presents a fruitful opportunity for science teachers to structure learning experiences through the use of explicit vocabulary instruction (Archer & Hughes, 2011).…”
Section: Effective Science Instruction For Swdmentioning
confidence: 99%
“…eading polysyllabic English words is important because these words make up the majority of those encountered in text (Kearns, Steacy, et al, 2016;Nagy & Anderson, 1984;Zeno, Ivens, Millard, & Duvvuri, 1995) and convey important academic concepts (Bryant, Ugel, Thompson, & Hamff, 1999). It is also difficult because polysyllabic words have greater variability and ambiguity in the pronunciation of their graphemes (Cummins & Port, 1998;Venezky, 1999).…”
mentioning
confidence: 99%
“…Therefore, it is natural if GMLM Model in reading literacy learning developed in this study proved to improve students' reading comprehension. Other experts who develop teaching reading based on students' activities that relevant to the GMLM Model are Bryant et al (2009), who concluded that the direct interaction of the student reading on pre, while, and post-reading stages will build students' knowledge about the material learned.…”
Section: The Contributions Of Gmlm Model Toward the Development Of Re...mentioning
confidence: 99%